Calcimimetic AMG-416 induced short-term changes in calcium concentrations and calcium isotope ratios in rats - Rott, Jeremy; Töpfer, Eva Teresa; Bartosova, Maria; Damgov, Ivan; Kolevica, Ana; Heuser, Alexander; Shroff, Rukshana; Zarogiannis, Sotirios G.; Eisenhauer, Anton; Schmitt, Claus P. (Biochemical and biophysical research communications, 2023)
Calcium (Ca) isotopes (δ44/42Ca) in serum and urine have been suggested as novel sensitive markers of bone calcification. The response of δ44/42Ca to acute changes in Ca homeostasis, has not yet been demonstrated. We measured serum Ca and δ44/42Ca in rats maintained on a standard and a 50% Ca reduced diet for 4 weeks, and after injection of 1 mg/kg of the calcimimetic AMG-416, 24 h prior to sacrifice. AMG-416 decreased serum Ca by a maximum of 0.38 ± 0.10 and 0.53 ± 0.35 mmol/l after 12 and 6 h, respectively, in the standard and low-Ca diet groups (p = 0.0006/0.02), while serum δ44/42Ca did not change over 24 h in both groups. Urinary Ca concentrations were higher 24 h after AMG-416 injection in both groups (p = 0.03/0.06), urine δ44/42Ca was not different compared to the untreated control groups. Our data does not show acute changes in δ44/42Ca in response to a single dose of AMG-416 within 24 h after injection, possibly due to a lack of bone calcification.